Performance of sulfur-based autotrophic denitrification and denitrifiers for wastewater treatment under acidic conditions. (December 2019) - Huang, Shan; Zheng, Zhaoming; Wei, Qingqing; Han, Il; Jaffé, Peter R.
Highlights: Autotrophic denitrification of NO3 − and NO2 − was achieved using S 2−, S2 O3 2−, and S 0 . Denitrification proceeded for S 2− and S2 O3 2− for pH 4–8, but for S 0 only when pH > 6. S 0 produced was not utilized in column experiments while S 2− was supplied. Activity narG and nirS genes were not affected by pH but that of the nirK gene was. The nirK -type denitrifiers are key in enabling acidic autotrophic denitrification. Abstract: Autotrophic denitrification under acidic conditions using sulfide (S 2− ), elemental sulfur (S 0 ), and thiosulfate (S2 O3 2− ) as electron donors are evaluated. Results from batch and column experiments show that when different S species were supplied, different pH conditions and denitrifier communities were required for denitrification to occur. Nitrate and nitrite were removed via autotrophic denitrification at pH ranging from 4 to 8, when S 2− or S2 O3 2− was the electron donor, while with S 0 denitrification was only observed at pH > 6. When S 2− was used as electron donor, it was converted to S 0, and S 0 was not used while S 2− was available. When addition of S 2− was discontinued, or S 2− depleted, S 0 that had accumulated was used as electron donor for denitrification. These findings demonstrate that sulfur-based autotrophic denitrification can proceed under acidic conditions, but that the addition of appropriate S species and the presence of an effective denitrifier community are required.